2013
DOI: 10.1186/1471-230x-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Looking for predictive factors of clinical response to adsorptive granulocyte and monocyte apheresis in patients with ulcerative colitis: markers of response to GMA

Abstract: BackgroundAdsorptive granulocyte and monocyte apheresis (GMA) with an Adacolumn in patients with ulcerative colitis (UC) has been applied as a non-pharmacological treatment strategy, but the efficacy has been encouraging as well as discouraging, depending on patients’ demography at entry. In this study, we looked for predictive factors for clinical response to GMA in patients with UC.MethodsIn a retrospective setting, 43 outpatients who had been treated with GMA for active UC were evaluated. Patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Hibi et al reported that higher baseline granulocyte fraction was an independent predictor of clinical response in GMA [18]. Low cumulative prednisolone doses, receiving GMA immediately after a clinical relapse, low WBC count at the first GMA session, and younger age were also reported as responders [26,27]. Our study also showed younger patients were responders.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Hibi et al reported that higher baseline granulocyte fraction was an independent predictor of clinical response in GMA [18]. Low cumulative prednisolone doses, receiving GMA immediately after a clinical relapse, low WBC count at the first GMA session, and younger age were also reported as responders [26,27]. Our study also showed younger patients were responders.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have shown that patients with a short duration of UC appeared to respond well to GMA [24,25,26]. Hibi et al reported that higher baseline granulocyte fraction was an independent predictor of clinical response in GMA [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received GMA therapy twice a week with the Adacolumn as previously described 12,17. The first patient evaluation was done after six GMA sessions.…”
Section: Methodsmentioning
confidence: 99%
“…The best responders seem to be steroid naive patients followed by steroid dependent patients or steroid refractory patients with a short history of disease [152,153] . A recent study tried to define predictive factors to identify patients with UC who are likely to respond to GMA [154] . In this trial 43 patients with active UC were enrolled.…”
Section: Granulocyte Monocyte Apheresismentioning
confidence: 99%